COVID‐19 and older adults with Down syndrome: Presentation, complications and risk for mortality. (31st December 2021) - Baksh, Asaad; Strydom, Andre; Sherman, Stephanie; Dierssen, Mara; Costa, Alberto; Huels, Anke; ,
Abstract: Background: Health conditions (including high rates of Alzheimer's disease, AD), immune dysfunction, and premature aging associated with trisomy 21 (Down syndrome, DS) may impact the clinical course of COVID‐19. Method: The T21RS COVID‐19 Initiative launched an international survey for clinicians or caregivers on patients with COVID‐19 and DS. Data collected between April and October 2020 (N=1046) were analysed and compared with the UK ISARIC4C survey of hospitalized COVID‐19 patients with and without DS. Result: Mortality rates in individuals with DS diagnosed with COVID‐19 showed a rapid increase from age 40 and were considerably higher in patients with DS (T21RS DS versus non‐DS patients: risk ratio (RR)=3.5 (95%‐CI=2.6;4.4), ISARIC4C DS versus non‐DS patients: RR=2.9 (95%‐CI=2.1;3.8)) even after adjusting for known risk factors for COVID‐19 mortality. Similar to the general population, the most frequent signs and symptoms of COVID‐19 were fever, cough, and shortness of breath. Joint/muscle pain and vomiting or nausea were less frequent (p<0.01), whereas altered consciousness/confusion were more frequent (p<0.01). Risk factors for hospitalization and mortality included age, male gender, diabetes, obesity, and AD, with the addition of congenital heart defects as a risk factor for hospitalization. Conclusion: Individuals with DS and COVID‐19 present with significantly higher rates of medical complications and mortality compared to general population peers, especially from age 40. The signs/symptoms of COVID‐19 and risk factors for severe disease course are similar to the general population. Those with dementia are at even greater risk, despite being younger than typical patients with AD. Individuals with Down syndrome should be prioritised for SARS‐Cov‐2 vaccination at younger ages than their peers in the general population.